Pars-plana Vitreous Tap for Phacoemulsification in the Eyes with Crowded Anterior Segment - Fazeela Qazi, Irfan Qayyum Malik Hafiza Sadia Imtiaz (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the efficacy of pars plana vitreous tap for safe accomplishment of phacoemulsification in eyes with severely crowded anterior segment. Study Design: Quasi-experimental study. Place and Duration of Study: Eye Department of DHQ-Teaching Hospital Gujranwala, from January 2014 to December 2017. Material and Methods: Patients of both genders, above 40 years of age who had crowded anterior segments and in whom viscoelastic substance could not deepen the anterior chamber sufficiently during cataract surgery (phacoemulsification) were included in this study. All patients underwent phacoemulsification and pars-plana vitreous aspirate of 0.1 ml taken 4 mm from the limbus in supero-temporal quadrant using 27-gauge needle. Results: 50 eyes of 40 patients with crowded anterior segment were included in this study. Sixteen (40%) were male and 24 (60%) were female. Average age noted was 54.3 ± 7.4 (range 48 – 65) years. Mean pre-op IOP recorded was 17.6 ± 2.3 (range 12 – 24.2) mm Hg, mean pre-op anterior chamber depth (ACD) of 2.1 ± 0.34 (range 1.6 – 2.6) mm and mean pre-op Axial length (AL) of 20.6 ± 0.45 (range 19.5 – 22.2) mm. Vitreous tap was successful in 42 eyes (84%) on first attempt and in remaining 8 eyes (16%), second attempt was required. Average volume of aspirated vitreous was 0.116 ± 0.03 (0.1 – 0.2) ml. The overall success rate was 100% with no per-op or post-op complications noted during follow up period of 6 months. Conclusions: Vitreous tap using needle is simple, safe, efficient and cost-effective technique for management of shallow anterior chambers during phacoemulsification. Key Words: Crowded anterior segment, axial length, anterior chamber depth, capsulorhexis, pars plana vitreous tap.